Genetic diversity of Cyprinion macrostomus (Heckel, 1843) populations in the Euphrates and Tigris rivers based on partial cytochrome b sequences of mitochondrial DNA - ParmaksÄ±z, Arif (Indian Journal of Fisheries, 2018)
Cyprinion macrostomus (Heckel, 1843), thriving in both Euphrates and Tigris river systems, is an economically important food fish species of the family Cyprinidae. It is important to know genetic structure of fis populations in terms of identification of genetic structure of stocks for facilitating sustainable fishing and conservation strategies.The present study, evaluated genetic structure of C. macrostomus populations in Euphrates and Tigris rivers using mtDNA cytochrome b sequence analysis. A total number of 44 C. macrostomus specimens were collected from Euphrates and Tigris rivers and total DNA was isolated from muscle tissue. Approximately 600 bp of mtDNA cyt b site was amplified by PCR and 8 polymorphic and 8 haplotypes were identified after sequence analysis. Mean haplotype and nucleotide diversity were calculated as 0.738 and 0.00253 respectively. Both populations had similar values in terms of haplotype as well as nucleotide diversity and neutrality tests were also found to be statistically insignificant.